2018
DOI: 10.1002/pbc.27292
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma in adolescents and young adults

Abstract: Cutaneous melanoma is rare in children, but has greater incidence in adolescents and young adults (AYAs). Diagnosis may be challenging due to its rarity in these age groups. Few studies have specifically addressed the topic of AYA melanoma. Though young-age melanoma may have particular biological characteristics, available data suggest that its clinical history is similar to that of adults. However, advances in treatment of adult melanoma have not been reflected in the treatment of AYAs. There is no standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 67 publications
0
32
0
2
Order By: Relevance
“…On the other hand, adults are more frequently diagnosed with nodular melanoma (NM) [9]. Indini et al showed that melanoma was more common in male patients above 39 years of age, whereas females were more commonly afflicted with melanoma when under 39 years of age [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, adults are more frequently diagnosed with nodular melanoma (NM) [9]. Indini et al showed that melanoma was more common in male patients above 39 years of age, whereas females were more commonly afflicted with melanoma when under 39 years of age [10].…”
Section: Introductionmentioning
confidence: 99%
“…Risk for melanoma increases with age overall, and older males are at higher risk compared to older females . However, melanoma is also the second most common malignancy among adolescents and young adults; in these populations, females are at increased risk . Other than age and gender, another primary risk factor for skin cancer is race/ethnicity, with increased susceptibility observed amongst non‐Hispanic whites (NHW) …”
mentioning
confidence: 99%
“…In general the reported sentinel node positivity rates are higher than those reported for adults (Offenmueller et al 2017;Balch et al 2014). In the event of nodal disease, complete lymph node dissection should be discussed (Indini et al 2018).…”
Section: Surgical Managementmentioning
confidence: 89%
“…Melanoma in children can be difficult to recognize and diagnose. There have been reports suggesting that primary cutaneous melanomas in children appear different from primary melanomas in adults; that some are atypical non-pigmented, thick lesions leading to late diagnosis of melanoma in children (Ferrari et al 2005;Indini et al 2018;Offenmueller et al 2017). The ABCDE rule (Asymmetry, irregular Borders, variegated Color, Diameter > 6 mm, and Evolution, meaning the tendency to change rapidly over weeks or months) might not suggest melanoma (Cordoro et al 2013).…”
Section: Clinical Presentation and Risk Factorsmentioning
confidence: 99%